PERFORMANCE MAHASISWA FAKULTAS EKONOMI UNIVERSITAS BATANGHARI JAMBI - R. Adisetiawan (Universitas Batanghari Jambi, 2014)
Object of this study were all students of the Economics Faculty of University Batanghari. They are the students of study management and IESP with active status following the lecture in the second semester of 2013/2014. Leave status and pass the final exam, excluding the population. The sampling technique used in this research were randomly. The results showed that student performance dimensions when viewed from the Faculty of Economics student attendance rates, student turns women tend to be more diligent students attend college than men. But when viewed according to the study program students tend to be more diligent management courses than courses IESP. Overall the students of the Faculty of Economics can be said to be classified as a diligent student who attended the lecture. In addition, they are more motivated to attend college also tend classified as a diligent student. When viewed from the dimensions GPA students of the Faculty of Economics, women tend to be better students than male students. Then when viewed according to the study program, tend to be better than the management courses courses IESP. In addition, students of the Faculty of Economics are much more motivated to attend college tend to have good value.Keywords: cumulative grade point